Bezpieczeństwo kardiologiczne w leczeniu astmy - Kuch, Marek (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Nowadays interdisciplinary problems become more and more important in medicine. Most, if not all the patients in real world are treated not on one isolated disease but two or more serious concomitant diseases. Therefore, it happens more and more often that medications used in treatment of one disease have adverse effects or are even harmful in the treatment of another disease. In the patients with cardiovascular and respiratory diseases medications acting on beta receptors are problematic. It is known that b-blockers, one of the main group of cardiac drugs, have beneficial effects on the heart but might cause bronchospasm in “respiratory” patients. On the other hand b-mimetics used in treatment of bronchial asthma might cause harmful tachycardia in cardiac patients. These complications or side effects of standard treatment of basic disease are partly reduced by the choice of medications acting selectively on appropriate b-receptors. The therapeutic compromise is needed between treatment of various concomitant diseases. Some other medications commonly used in treatment of cardiovascular disease might have adverse effects on respiratory system (aspirin, angiotensin converting enzyme inhibitors, amiodarone). Tachycardia is often observed during the treatment with fosfodiesterase inhibitors (methyloxanthine) administered to the patients with respiratory diseases. Drug interactions that result from the administration of various active medications for different diseases in one patient are also problematic. Despite medicine development there is still the problem of finding the golden mean in interdisciplinary treatment.